(untitled) (Research, Society and Development, 2021)
Gummy smile is a clinical condition in which a gingival exposure greater than 4mm occurs when smiling, aesthetically affecting many individuals. Gummy smile is due to multifactorial etiological conditions; that is why, for its correction, a correct diagnosis must be established, determining the etiological factor (s) to carry out an effective treatment plan. The following is a case report of a 24-year-old woman who presented extensive gingival exposure when smiling due to a hypermobile lip and an altered passive eruption, for which a gingivectomy was performed in combination with the lip repositioning technique, eliminating a band of mucosa of the maxillary vestibule creating a partial thickness flap between the junction of the mucogingival line and apical to the upper lip musculature to later suture and achieve a shorter vestibule, restricting the upper lip musculature giving resolution to the excessive gingival display. It is concluded that both procedures were successful, predictable, and minimally invasive, obtaining a satisfactory result without reporting relapses in 6 months.